2005
DOI: 10.1152/ajpregu.00620.2004
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex regulation of renal sympathetic nerve activity and heart rate in renal wrap hypertensive rats

Abstract: Despite its usefulness as a nongenetic model of hypertension, little information is available regarding baroreflex function in the Grollman, renal wrap model of hypertension in the rat. Baroreflex regulation of renal sympathetic nerve activity (RSNA) and heart rate (HR) were studied in male, Sprague-Dawley rats hypertensive (HT) for 1 or 4-6 wk after unilateral nephrectomy and figure-8 ligature around the remaining kidney or normotensive (NT) after sham surgery. Rats were anesthetized with Inactin and RSNA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Furthermore, the magnitudes of the maximum and minimum reflex changes in RSNA relative to the RSNA value at the midpoint in our study were also very similar to those in the conscious rat (16). The range of the evoked baroreflex changes in HR in our study, however, as in previous studies in anesthetized rats (24,29), was less than that observed in the conscious rat (16,24,29). Nevertheless, our results do not indicate that disinhibition of DMH or PeF neurons reduces the sensitivity of the cardiac component of the baroreceptor reflex.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the magnitudes of the maximum and minimum reflex changes in RSNA relative to the RSNA value at the midpoint in our study were also very similar to those in the conscious rat (16). The range of the evoked baroreflex changes in HR in our study, however, as in previous studies in anesthetized rats (24,29), was less than that observed in the conscious rat (16,24,29). Nevertheless, our results do not indicate that disinhibition of DMH or PeF neurons reduces the sensitivity of the cardiac component of the baroreceptor reflex.…”
Section: Discussionsupporting
confidence: 88%
“…As a result of these two factors, the overall contribution of C-fiber afferents to baroreflex regulation may increase in HT relative to A-fiber inputs. In 4-wk HT rats, the baroreflex curve relating renal sympathetic nerve discharge to MAP is shifted to the right with no change in gain, while the curve relating HR to MAP is shifted to the right with a reduced gain (Vitela et al 2005). The relative role of C-fiber versus A-fiber baroreceptor afferent inputs to specific aspects of reflex function remains to be determined.…”
mentioning
confidence: 97%
“…This enhanced postsynaptic baclofen effect could contribute to the enhanced baclofen-induced pressor response observed in chronic hypertension and altered baroreflex function in hypertension. 14 …”
mentioning
confidence: 99%